Factors associated with citations of articles on circular economy in the Web of Science: modeling for main publishers - Minchón-Medina, Carlos Alberto; Timaná-Palacios, Daphne Jannet; Alvarez-Risco, Aldo; Del-Aguila-Arcentales, Shyla; Yáñez, Jaime A. (Frontiers in Artificial Intelligence, 2023)
Introduction The publication of articles on the circular economy has different associated factors to explain the citations registered in the Web of Science. Method Articles from the publishers Elsevier, MDPI, Taylor & Francis, Wiley, and Springer Nature were evaluated. Results It was expected that the older the article was, the more citations it had received, but this was not always the case. It was also recognized that there was a lower number of citations if the articles were too large or if they had too many references. Discussion This analysis helps to establish the factors that must be addressed in order to publish in journals that have a high citation rate. Conclusion: Based on speci?c articles and with speci?c references, it will be possible to increase the probability of citations.